The Fourth Estate : Journalism in twentieth-century Ireland - O'Brien, Mark, 1973- (Book collections on Project MUSE., 2017)
This book examines the history of journalists and journalism in twentieth-century Ireland. While many media institutions have been subjected to historical scrutiny, the professional and organisational development of journalists, the changing practices of journalism, and the contribution of journalists and journalism to the evolution of modern Ireland have not. This book rectifies the deficit by mapping the development of journalism in Ireland from the late 1880s to today. Placing the experiences of journalists and the practice of journalism at the heart of its analysis, it examines, for the first time, the work of journalists within the ever-changing context of Irish society. Based on strong primary research - including the previously un-consulted journals and records produced by the many journalistic representative organisations that came and went over the decades - and written in an accessible and engaging style, The Fourth Estate will appeal to anyone interested in journalism, history, the media and the development of Ireland as a modern nation.